Enterprise information systems : 17th International Conference, ICEIS 2015, Barcelona, Spain, April 27-30, 2015, Revised selected papers /: 17th International Conference, ICEIS 2015, Barcelona, Spain, April 27-30, 2015, Revised selected papers. (2015) - Unknown
No abstract available